Qualidade e potencial antioxidante de frutas nativas do litoral cearense em diferentes estádios de maturação. - Façanha, Rafaela Vieira (2012)
The objective of this work was to characterize physical, chemical and physico-chemical and evaluate the total antioxidant activity of fruits of viuvinha (Myrcia splendens (Sw.) DC.), mapirunga (Eugenia tinctoria Gagnep.) and araticum-do-brejo (Annona glabra L.) from the coastal vegetation of Ceará, at different stages of maturation. Fruits were physically characterized by size, color, total weight, yield, and firmness. For the evaluation of the physico-chemical and chemical analyzes were made as follows: soluble solids (SS), acidity, pH, SS / TA ratio, total soluble sugars and reducing sugars, soluble pectin, vitamin C, chlorophyll and total carotenois, anthocyanins and yellow flavonoids , total extractable polyphenols (TEP) and total antioxidant activity (TAA) by ABTS method. The study found that the fruits of viuvinha and mapirunga showed an increase in total weight, length, diameter and yield of the pulp during ripening. In fruits of araticum observed a decrease in these parameters at the end of maturation. Were also observed an increase in soluble solids, SS / TA ratio, total soluble sugars, reducing sugars in the fruits analyzed as starch hydrolysis occurred. Only the fruits of viuvinha there was a decrease in acidity during the ripening. There solubilization of pectin during ripening, except in the fruits of mapirunga. Among the bioactive compounds reported an increase in vitamin C during ripening of fruits analyzed. There was a high content of anthocyanins in late-stage of viuvinha and mapirunga. Only in the fruits of viuvinha there were yellow flavonoids during ripening. Emphasis was placed high values of extractable polyphenols and total antioxidant activity in fruits of viuvinha and mapirunga. There was significant positive correlation between total antioxidant activity and total extractable polyphenol content of all species analyzed. The pulp of viuvinha and mapirunga are promising in view of considerable amounts of bioactive compounds such as carotenoids, anthocyanins, yellow flavonoids and total polyphenols total extractable differentials that make products on the market of native fruits.